EULAR definition of erosive disease in light of the 2010 ACR/EULAR rheumatoid arthritis classification criteria. Issue 4 (2nd February 2013) - van der Heijde, Désirée; van der Helm-van Mil, Annette H M; Aletaha, Daniel; Bingham, Clifton O; Burmester, Gerd R; Dougados, Maxime; Emery, Paul; Felson, David; Knevel, Rachel; Kvien, Tore K; Landewé, Robert B M; Lukas, Cédric; et al.
Abstract : The aim of this report was to propose a definition for erosive disease in the context of inflammatory arthritis in light of the 2010 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) rheumatoid arthritis (RA) criteria for use in clinical practice and studies. A EULAR task force was formed including 16 rheumatologists and one rheumatology fellow. The process was both evidence based and consensus based, and included, between March 2010 and April 2012, analyses of data from two cohorts, two face-to-face meetings, one online voting and one teleconference. The Leiden Early Arthritis Cohort and the French ESPOIR cohort were used for the evidence-based part. The outcome measures, which were initiation of methotrexate therapy, or any disease-modifying antirheumatic drug therapy within the first year of disease and arthritis persistency over 5 years, were studied with the aim to give the best definition of erosive disease. A decision was made to select a definition with a high specificity and focus on patients who did not otherwise fulfil the 2010 ACR/EULAR RA criteria (<6 points). By a unanimous vote the following definition was selected: erosive disease for use in the 2010 ACR/EULAR RA classification criteria is defined when an erosion (defined as a cortical break) is seen in at least three separate joints at any of the following sites: the proximal interphalangeal, the metacarpophalangeal, the wrist (counted as one joint) and the metatarsophalangeal joints on radiographs of both hands and feet. A highly specific definition for erosive disease has thus been formulated.